Effect of blood pressure and glycemic control on the plasma cell-free DNA in hemodialysis patients - Da Wun Jeong; Ju-Young Moon; Young-Wook Choi; Haena Moon; Kipyo Kim; Yu-Ho Lee; Se-Yeun Kim; Yang-Gyun Kim; Kyung-Hwan Jeong; Sang-Ho Lee (The Korean Society of Nephrology, 2015)
Background: The plasma levels of cell-free DNA (cfDNA) are known to be elevated under inflammatory or apoptotic conditions. Increased cfDNA levels have been reported in hemodialysis (HD) patients. The aim of this study was to investigate the clinical significance of cfDNA in HD patients. Methods: A total of 95 patients on HD were enrolled. We measured their predialysis cfDNA levels using real-time EIF2C1 gene sequence amplification and analyzed its association with certain clinical parameters. Results: The mean plasma cfDNA level in the HD patients was 3,884 ± 407 GE/mL, and the mean plasma cfDNA level in the control group was 1,420 ± 121 GE/mL (P < 0.05). Diabetic patients showed higher plasma cfDNA levels compared with nondiabetic patients (P < 0.01). Patients with cardiovascular complications also showed higher plasma cfDNA levels compared with those without cardiovascular complication (P < 0.05). In univariable analysis, the cfDNA level was associated with 3-month mean systolic blood pressure (SBP), white blood cell, serum albumin, creatinine (Cr), normalized protein catabolic rate in HD patients. In diabetic patients, it was significantly correlated with SBP, hemoglobin A1c, and serum albumin. In multivariate analysis, SBP was the independent determinant for the cfDNA level. In diabetic patients, cfDNA level was independently associated with hemoglobin A1c and SBP. Conclusions: In patients with HD, cfDNA is elevated in diabetic patients and patients with cardiovascular diseases. Uncontrolled hypertension and poor glycemic control are independent determinants for the elevated cfDNA. Our data suggest that cfDNA might be a marker of vascular injury rather than proinflammatory condition in HD patients.